The Chalcolithic at Mersin - Yumuktepe (İstanbul)
192 sayfa
Keywords: “The final publication of Level XVI at Mersin-Yumuktepe is the terminal step of a long-term project. The aim of this publication is to integrate the data obtained by J. Garstang during the excavations conducted at Mersin-Yumuktepe (1936-39 and 1946-47) and published in 1953 in the monograph “Prehistoric Mersin”, with those produced during the excavations carried out from 1993 to 2004, under the direction of I. Caneva, for a comprehensive reconstruction of one of the most notorious levels of occupation at Yumuktepe. The long prehistoric occupational sequence reconstructed by Garstang, the first to have been established in the archaeology of Cilicia, quickly became one of the main references in the Near Eastern, Levantine and East Mediterranean archaeology. In this framework, the unique evidence represented by the “Citadel” of the Level XVI was often considered as a “hall-mark” of Yumuktepe and a recurring “topos” of the archaeological discourse dealing with the chalcolithic societies of the region. To confront with such a “giant” of the Near Eastern archaeology and with the heritage left by Garstang has not been an easy task. The integration of heterogeneous data produced in the frame of different practices, epistemologies and narratives of archaeology has required a long, continuous and sometimes quizzical process of interpolation and negotiation between past and present archaeological evidence aimed at a detailed and attentive reconstruction of the economic, social and cultural developments of the Early-Chalcolithic community at Yumuktepe“ -- Yayıncı.